Budaya Perusahaan pada Wirausaha Muda Mahasiswa Kewirausahaan Universitas Teknologi Sumbawa - Fadli Faturrahman (Jurnal Riset dan Inovasi Manajemen, 2026)
The development of student entrepreneurship has become an important strategy in encouraging young generations to become independent, creative, and capable of creating economic opportunities. However, business success is not only determined by technical abilities such as production, marketing, and financial management but also by the ability to develop corporate culture as the foundation of organizational behavior. Corporate culture plays an important role in shaping shared values, responsibility, collaboration, and organizational adaptation. This study aims to analyze the process of corporate culture formation among student entrepreneurs in the Entrepreneurship Study Program at Universitas Teknologi Sumbawa. This research employed a qualitative approach using a case study method. The research participants consisted of five groups of students actively managing entrepreneurial activities. Data were collected through in-depth interviews, observation, and documentation. Data analysis followed the Miles, Huberman, and Saldaña interactive model consisting of data condensation, data display, and conclusion drawing. The findings indicate that corporate culture among student entrepreneurs is developed through several important aspects, including shared values, collaborative work culture, innovation orientation, group leadership, and adaptation to business challenges. Students not only learn how to operate businesses but also begin to develop organizational identities through values of responsibility, creativity, communication, and commitment. This study highlights that entrepreneurship education in higher education should expand its learning orientation beyond business creation skills toward organizational culture development as an important foundation for sustainable entrepreneurship.